Vive la révolution animale!: an ethnography of the social consumer movement of vegetarianism - Barboza, Renata Andreoni (2017)
This dissertation aims to provide an improved understanding of the social consumer movement of vegetarians and vegans, while it summarizes the results of three studies that, taken together, fulfill the twin objectives of analyzing the revolution in videography and analyzing marketplace exclusion. In the first study, the central role of marketplace exclusion in the social consumer movement of vegetarianism in the city of São Paulo is discussed, and the commitment of vegetarians based on their individualized forms of participation and their focus on cultural change is described. The second study of this dissertation discusses the technique of videography and its application to the practice of academic and market research, presenting a protocol that summarizes the rich and detailed understanding of this method in practice. The third study is an example of a published videography that uses realistic conflict theory to observe how different types of people connected with vegetarianism and veganism deal with conflicts within and outside the movement and how these conflicts affects market dynamics. The data are based on 12 months of ethnographic immersion fieldwork that involved visits to 18 vegetarian events, five public demonstrations on the street, and regular visits to five different vegan restaurants, in order to observe and talk to vegetarians and vegans on-site. Extended interviews were conducted with 6 ovo-lacto vegetarians and 27 vegans. The paper concludes with a discussion of the main theoretical contributions, managerial implications, implications for public policy, and limitations and suggestions for further research.